Cuidado espiritual em enfermagem: contribuição para a educação acadêmica segundo o pressuposto filosófico de Callista Roy - Navarine, Teresa Cristina Rosa Romero (2015)
This study aimed to assess the understanding of nursing students about the process of nursing care, which determine the understanding of these on the spiritual nursing care, identify whether to offer patients a spiritual nursing care from the Understanding these, describe the proposed curriculum of this institution is developed in order to favor a committed practice with the human being as a whole, involving spiritual care, and identify if people cared for by students in traineeship presented or shown to have a relationship mutual with the world and with God. This is a field research, descriptive, with a qualitative approach, having as a scope a nursing theory based on interactive process proposed by Dr. Callista Roy, who takes as a philosophical assumption that people have mutual relationships with the world and with God. The research was conducted at the Federal University of Paraíba, linked to the Health Sciences Centre and Department of Clinical Nursing, precisely in Nursing Techniques Laboratory, located in the city of João Pessoa / PB. The study gathered six nursing students of the tenth period selected by the inclusion criteria. Data were collected consecutively to the approval of this research by the Ethics Committee, under CAAE No 35391514.3.0000.5188. Therefore, with respect to data collection, it was held in October 2014, under the guidance of a form containing relevant issues to the study objectives, pointing out that, for the record data, a recording system was used audio, previously clarified as consentimento. Já term the technique used for this purpose was the focal group. Data analysis occurred through the Bardin content analysis technique. It was observed that the students correlate the care process with the exhibition held in the classroom and as enabler tool of development of their motor skills, rather than reflections on the essence of care. Thus, they did not know and need to set directly spiritual nursing care; before, correlated with spirituality and religiosity. Unanimously affirmed the importance of offering patients a spiritual nursing care, but the immaturity of the clinical practice, have not done due to numerous technical procedures to be performed, while also stating that the proposed curriculum of this institution favored this learning and, finally, that all people cared for them had a mutual relationship with the world and with God. However, it is nurses to perform and understand the importance of spiritual care, to exercise it continuously to view the inseparably patient, as it really is, taking into account their ethical and moral values grounded in pointing to a practice based on the scientific rigor, but also the love and commitment for others, moving away from the daily care mechanistic justified by arguments failed.